The Pkn22 Kinase of Nostoc PCC 7120 Is Required for Cell Differentiation via the Phosphorylation of HetR on a Residue Highly Conserved in Genomes of Heterocyst-Forming Cyanobacteria - Roumezi, Baptiste; Xu, Xiaomei; Risoul, Véronique; Fan, Yingping; Lebrun, Régine; Latifi, Amel (Frontiers in Microbiology, 2020)
Hanks-type kinases encoding genes are present in most cyanobacterial genomes. Despite their widespread pattern of conservation, little is known so far about their role because their substrates and the conditions triggering their activation are poorly known. Here we report that under diazotrophic conditions, normal heterocyst differentiation and growth of the filamentous cyanobacterium Nostoc PCC 7120 require the presence of the Pkn22 kinase, which is induced under combined nitrogen starvation conditions. By analyzing the phenotype of pkn22 mutant overexpressing genes belonging to the regulatory cascade initiating the development program, an epistatic relationship was found to exist between this kinase and the master regulator of differentiation, HetR. The results obtained using a bacterial two hybrid approach indicated that Pkn22 and HetR interact, and the use of a genetic screen inducing the loss of this interaction showed that residues of HetR which are essential for this interaction to occur are also crucial to HetR activity both in vitro and in vivo. Mass spectrometry showed that HetR co-produced with the Pkn22 kinase in Escherichia coli is phosphorylated on Serine 130 residue. Phosphoablative substitution of this residue impaired the ability of the strain to undergo cell differentiation, while its phosphomimetic substitution increased the number of heterocysts formed. The Serine 130 residue is part of a highly conserved sequence in filamentous cyanobacterial strains differentiating heterocysts. Heterologous complementation assays showed that the presence of this domain is necessary for heterocyst induction. We propose that the phosphorylation of HetR might have been acquired to control heterocyst differentiation.